2005
DOI: 10.1093/carcin/bgi259
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of EphB2 that parallels invasion and metastasis in colorectal tumours

Abstract: EphB2, a receptor tyrosine kinase regulated by the beta-catenin/Tcf4 complex, is expressed in the proliferative compartment of mouse intestine and regulates bidirectional migration of intestinal precursor cells in the crypt-villus axis through repulsive interaction with Ephrin-B ligands. Recently, it has been shown that reduction of EphB activity accelerates colon tumour progression in the Apc(Min/+) mice. In this study, we examined the expression of EphB2 in normal colon, adenomas, primary colorectal cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 29 publications
13
100
0
1
Order By: Relevance
“…MAP4K3 is a component in the nutrient-responsive pathway affecting cell growth (Findlay et al 2007). Deregulated expression of various EPH receptors, including EPHB2, has been reported in diverse tumor types (Guo et al 2006;Jubb et al 2005). All of these results suggested that KRAP might play critical roles in cancer-associated signaling pathways, including Ras, MAPKs (MAP kinases), integrins, EPH receptors, and protein kinase C.…”
Section: Gene Expression Profile By Inhibiting Krap Expression In Hctmentioning
confidence: 86%
“…MAP4K3 is a component in the nutrient-responsive pathway affecting cell growth (Findlay et al 2007). Deregulated expression of various EPH receptors, including EPHB2, has been reported in diverse tumor types (Guo et al 2006;Jubb et al 2005). All of these results suggested that KRAP might play critical roles in cancer-associated signaling pathways, including Ras, MAPKs (MAP kinases), integrins, EPH receptors, and protein kinase C.…”
Section: Gene Expression Profile By Inhibiting Krap Expression In Hctmentioning
confidence: 86%
“…Thereafter, the slides were placed in washing buffer (10 mM Tris-HCl, 0.85% NaCl, 0.1% bovine serum albumin, pH 7.4). After antigens were retrieved by boiling the tissue sections in 10 mM citrate buffer for 20 min in the microwave oven, consecutive sections were incubated with rabbit polyclonal BTF3a/b antibodies (Zymed Laboratories, Inc., Karlsruhe, Germany), goat polyclonal EPHB2 antibodies (R&D systems, Wiesbaden-Nordenstadt, Germany), 18 or normal rabbit or goat IgG (DAKO) as negative controls in an antibody diluent with background-reducing components (DAKO) at 4˚C overnight. For BTF3 and EPHB2 detection, the slides were incubated with HRPO-conjugated anti-rabbit IgG (Amersham International, Buckinghamshire, UK) and anti-goat IgG (Invitrogen GmbH, Karlsruhe, Germany), respectively, for 1 h at room temperature.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Although primarily involved in mediating developmental events directed by Ephrin (17), particularly in the nervous system, many studies have indicated a direct role for the ephrins and their receptors in tumor progression and angiogenesis (18). Increased expression of Ephrins and their receptors have been correlated with survival and invasive capacity of colorectal and ovarian cancers (19)(20)(21). Additionally, EphA2 and EphB2 have emerged as attractive drug targets for cancer therapy (22,23).…”
Section: Detection Of Copy Number Alterations In the Genomes Of Mousementioning
confidence: 99%